An artificial immune system approach to automated program verification: Towards a theory of undecidability in biological computing - Banerjee, Soumya (PeerJ Preprints, 2017)
An immune system inspired Artificial Immune System (AIS) algorithm is presented, and is used for the purposes of automated program verification. Relevant immunological concepts are discussed and the field of AIS is briefly reviewed. It is proposed to use this AIS algorithm for a specific automated program verification task: that of predicting shape of program invariants. It is shown that the algorithm correctly predicts program invariant shape for a variety of benchmarked programs. Program invariants encapsulate the computability of a particular program, e.g. whether it performs a particular function correctly and whether it terminates or not. This work also lays the foundation for applying concepts of theoretical incomputability and undecidability to biological systems like the immune system that perform robust computation to eliminate pathogens.
Keywords: Artificial Immune System; Evolutionary Computing; Program Invariant; Automatic Program Verification; Shape of Invariant; Undecidability; Incomputability; Biological Computing; Immuno-computing